Association of dietary calcium intake at dinner versus breakfast with cardiovascular disease in U.S. adults: the national health and nutrition examination survey, 2003-2018 - Ting Zhang; Sijia Zhuang; Yue Yu; Zizhuo Fan; Xiyun Ren (BMC, 2024)
Abstract Background Currently, it is still largely unknown whether the proportion of calcium intake at breakfast and dinner is associated with cardiovascular disease (CVD) in the general population. Objectives The aim of this study was to evaluate the association of dietary calcium intake at dinner versus breakfast with CVD in a nationally representative sample of US adults. Methods The study population consisted of 36,164 US adults (including 4,040 CVD cases) from the NHANES 2003 to 2018. According to the ratio of dietary calcium intake at dinner and breakfast (Δ = dinner/breakfast), 36,164 participants were divided into five groups. After adjustment for a series of confounder factors, logistic regression analyses were performed to examine the association between Δ and CVD. Dietary substitution models were used to explore the changes in CVD risk when a 5% dietary calcium intake at dinner was substituted with dietary calcium intake at breakfast. Results Compared with participants in the lowest quintile, participants in the highest quintile were more likely to have CVD, with an adjusted OR of CVD of 1.16 (95% CI, 1.03 to 1.31). When the total calcium intake remained constant, replacing a 5% dietary calcium intake at dinner with dietary calcium intake at breakfast was associated with a 6% lower risk of CVD. Conclusions Compared to the lowest quintile of Δ, participants in the highest quintile of Δ were likely to experience CVD in the general population. It is necessary to scientifically allocate dietary calcium intake at breakfast and dinner.